2008
DOI: 10.1051/0004-6361:20078748
|View full text |Cite
|
Sign up to set email alerts
|

The stellar content of the Hamburg/ESO survey

Abstract: We present the quantitative methods used for selecting candidate metal-poor stars in the Hamburg/ESO objective-prism survey (HES).The selection is based on the strength of the Ca ii K line, B − V colors (both measured directly from the digital HES spectra), as well as J − K colors from the 2 Micron All Sky Survey. The KP index for Ca ii K can be measured from the HES spectra with an accuracy of 1.0 Å, and a calibration of the HES B − V colors, using CCD photometry, yields a 1-σ uncertainty of 0.07 mag for star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
198
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 186 publications
(202 citation statements)
references
References 50 publications
(63 reference statements)
1
198
0
Order By: Relevance
“…The majority of our programme stars are selected from the Hamburg/ESO survey of Christlieb and collaborators (HES;Christlieb et al 2008) with the addition of one star from the HK survey, CS 30301−015. The CEMP star LP 625−44 was added since it is well studied, and previous authors have suggested that it might be a CEMP-r/s star.…”
Section: Sample Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of our programme stars are selected from the Hamburg/ESO survey of Christlieb and collaborators (HES;Christlieb et al 2008) with the addition of one star from the HK survey, CS 30301−015. The CEMP star LP 625−44 was added since it is well studied, and previous authors have suggested that it might be a CEMP-r/s star.…”
Section: Sample Definitionmentioning
confidence: 99%
“…Carbon-enhanced metal-poor (CEMP) stars were originally identified among the VMP and EMP stars discovered in the HK survey of Beers, Preston, & Shectman (Beers et al 1985, 1992 and the Hamburg/ESO survey of Christlieb and collaborators (Christlieb et al 2008), and supplemented by a number of surveys since. The fraction of CEMP stars rises with decreasing metallicity (conventionally tracked by the iron abundance, [Fe/H]); hence they are of particular importance for studies of the early chemical evolution of the Galactic halo.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the deepest survey for searching metal-poor stars was the Hamburg/ESO Survey (HES), which reached V ≈ 16 (Christlieb et al 2008), which increased the number of known metal-poor stars ([Fe/H] < −3.0) by about a factor of two with respect to all previous surveys. In terms of overall metallicity Z, or [M/H], the most metal-poor stars known were the giants CD −38 • 245 ([Fe/H] = −4.1), CS 22885-096, BS 16467-062, and CS 22172-002 with [Fe/H] ≈ −3.8 (François et al 2003;Cayrel et al 2004), and also the turn-off binary star CS 22876-32 (Norris et al 2000;González Hernández et al 2008) with [Fe/H] ≈ −3.7.…”
Section: Introductionmentioning
confidence: 99%
“…We also investigate the reliability of multiple Th/X chronometers for HE 2327−5642, where X is an element in the Ba−Hf range. HE 2327−5642 was identified as a candidate metal-poor star in the Hamburg/ESO Survey (HES; see Christlieb et al (2008) for details of the candidate selection procedures). Moderateresolution (Δλ = 2 Å) spectroscopy obtained at the Siding Spring Observatory (SSO) 2.3 m-telescope with the Double Beam Spectrograph (DBS) confirmed its metal-poor nature.…”
Section: Introductionmentioning
confidence: 99%